Ko te maoopopo ko te lima malohi. Collaboration is our strength. (Kairaranga, 2008)
A delegation from the Ministry of Education, Special Education (GSE) went to Tokelau in 2007 in response to a request from the Tokelauan government to help establish services for children with special education needs. The team was led by Ezra Schuster and made up of a special education advisor, a speech-language therapist, an advisor on deaf children, and a physiotherapist. This article discusses the work of this team and describes their unique, challenging and incredibly fulfilling experience.